Collagen and chitosan blends for 3D bioprinting: A rheological and printability approach. (February 2020) - Heidenreich, Ana Carolina; Pérez-Recalde, Mercedes; González Wusener, Ana; Hermida, Élida Beatriz
Abstract: Collagen and chitosan are widely employed as biomaterials, including for 3D-bioprinting. However, the use of collagen and chitosan (col:chi) blends as bioinks is still scarce. In this work, the rheology of different hydrogel precursors (0.5–1.50% w/v chi: 0.18–0.54% w/v col) was analyzed through frequency and strain sweeps, as well as at different shear rates. Col:chi blends showed a shear-thinning behavior, with viscosity values at low shear rates between 0.35 and 2.80 Pa s. Considering the strain rate determined by the applied flow in a 3D-bioprinter, precursor viscosities during the extrusion were in the interval 0.5–0.8 Pa s. Printability (Pr) was measured comparing images of the printed meshes and the corresponding CAD grid design, using photograph analysis. Col:chi 0.36:1.00 was chosen to print mono-layered scaffolds for tissue engineering (TE) because of its suitable viscosity, printability and polymer ratio content. Hydrogels were obtained through NaHCO3 nebulization and 37° incubation, and NHS/EDC were added to obtain scaffolds with improved mechanical behavior. They were stable after 44 h in PBS with collagenase at physiological level and showed no cytotoxic effect in NIH-3T3 fibroblasts. Highlights: 3D-bioprinting is a powerful emerging field in which ink composition is a critical issue. Collagen and chitosan are very well-known biopolymers. Blends of collagen and chitosan composing a bioink are poorly explored. Collagen and chitosan blends behavior through a 3D-bioprinter were assessed in this work. Printed and crosslinked scaffolds for tissue engineering were obtained from col:chi 0.36:1.00, both % w/v.